Faktor-Faktor yang Mempengaruhi Kinerja Guru SMK Bidang Produktif Pasca Sertifikasi - Sutopo Sutopo (Department of Mechanical Engineering Education, 2017)
This study aimed to quantitatively describe the variables of certification's impact, teachers' workability, work motivation, work commitment, and teacher performance on Vocational High School (SMK) teachers after the teacher certification program is implemented. This study uses quantitative methods to obtain measurable data that is descriptive, comparative and associative and to answer the problem formulation and research questions. The descriptive analysis of a portion of the research data resulted in research findings which show: (1) The impact of SMK teachers certification, which were developed from the pride, professionalism, and welfare aspects; obtain information that 34% are categorized as very good, 58% are in good category, 6% are in moderate category and 2% are in poor category, (2) the teachers' workability which were developed from the aspects of pedagogical competence, professionalism, personality and social, obtain information that 32% are categorized as very good, 60% are good, 6% are moderate and 2% are in poor category, (3) teachers' work motivation which were indicated from the aspects of needs of achievement, existence and power, affiliation, self-actualization and independence, and growth expectations, obtained information that 24% are categorized as very good, 60% are in good category, and 16% are in moderate category, (4) work commitment of teachers which were developed from the aspects of affective commitment, continuity and normative, obtained findings that 26% are in very good category, 64% are good, and 10% are in moderate category, (5) the performance of SMK teachers which were developed from the aspects of fulfillment of the main duties, implementation of duties other than the main duties, and professional development, obtained information that 20% are categorized as very good, 64% are in good category, and 16% are in moderate category. Penelitian ini bertujuan mendeskripsikan secara kuantitatif variabel dampak sertifikasi, kemampuan kerja guru, motivasi kerja guru, komitmen kerja guru, dan kinerja guru SMK setelah mengikuti program sertifikasi guru. Penelitian ini menggunakan metode kuantitatif untuk memperoleh data terukur yang bersifat deskriptif, komparatif dan asosiatif. Hasil analisis secara deskriptif sebagian data hasil penelitian menunjukkan bahwa: (1) Dampak sertifikasi guru SMK yang dikembangkan dari aspek kebanggaan, keprofesionalan dan kesejahteraan diperoleh informasi sebesar 34% termasuk kategori amat baik, 58% termasuk kategori baik, (2) kemampuan kerja guru yang dikembangkan dari aspek kompetensi pedagogis, professional, kepribadian dan sosial diperoleh informasi sebesar 32% termasuk kategori amat baik, 60% kategori baik, (3) motivasi kerja guru yang diindikasikan dari aspek kebutuhan berprestasi, eksistensi dan berkuasa, berafiliasi, aktualisasi dan kemandirian, dan harapan pertumbuhan diperoleh informasi sebesar 24% termasuk kategori amat baik, 60% termasuk kategori baik, (4) komitmen kerja guru yang dikembangkan dari aspek komitmen afektif, kontinuitas dan normatif diperoleh temuan sebesar 26% termasuk aktegori amat baik, 64% termasuk kategori baik, (5) kinerja guru SMK yang dikembangkan dari aspek pelaksanaan tugas pokok, pelaksanaan tugas di luar tugas pokok dan pengembangan keprofesionalan diperoleh informasi sebesar 20% termasuk kategori amat baik, 64% termasuk kategori baik.